INTEGRATING UNIVERSAL DESIGN FOR LEARNING AND DIGITAL TECHNOLOGY: ADVANCING INCLUSIVE EDUCATION IN THE 21ST CENTURY - Mayasari, Linda Ika; Dulyapit, Apit; Yunitasari, Septiyani Endang; Syam, Aldo Redho (Irfani, 2025)
The purpose of this article is to comprehensively examine the integration of Universal Design for Learning (UDL) principles and digital technology within the context of 21st-century inclusive education through a narrative literature review. This study employs a narrative literature review method with a qualitative and exploratory approach. The data sources consist of 15 international journal articles published between 2023 and 2025. The research instrument is a manually developed data extraction sheet used to gather information from each article. Data analysis utilizes qualitative thematic analysis with a deductive approach, referencing the UDL theoretical framework. The results of this study: (1) Teachers' knowledge and attitudes towards inclusion remain limited and inconsistent; (2) Structural and policy limitations hinder the implementation of inclusive education; (3) The role of digital technology in supporting the application of UDL to create flexible and adaptive learning; and (4) Issues of access and social justice in higher education, particularly for vulnerable groups such as refugees and individuals with disabilities. This study implies that 21st-century inclusive education cannot be separated from digital transformation and flexible learning design paradigms such as UDL. Technology is positioned not just as an assistive tool but as a structural foundation for designing learning that is responsive to diversity. Approaches based on quality of life, cultural intelligence, and recognition of the socio-political context of learners are key elements in the development of a substantively inclusive educational system.